2005
DOI: 10.1021/ja0458165
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Putative Möbius Aromatic Hydrocarbon. The Effect of Benzannelation on Möbius [4n]Annulene Aromaticity

Abstract: The first experimental example of a [4n]annulene derivative with one Mobius twist, 1, was synthesized recently [Ajami, D.; Oeckler, O.; Simon, A.; Herges, R. Nature 2003, 426, 819] and was purported to possess aromatic character. However, critical analysis of the published crystallographic data indicates that the Mobius [16]annulene core of 1 shows large bond alternation (Deltar up to 0.157 A). Delocalization in this core is inhibited by large dihedral angles, which hinders effective pi overlap. This conclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
117
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(127 citation statements)
references
References 58 publications
6
117
1
2
Order By: Relevance
“…The synthesized Möbius ring lies ∼ 2 kcal/mol above and has the structure anti − tZcZcZt shown in Figure 43 with C 2 symmetry [255]. It has been argued [258] about aromaticity of this system, on the basis of the bond alternation resulting from crystal data [255] and of large dihedral angles inhibiting the overlap between π orbitals. In contrast, the principal component analysis performed on the 153 most stable structures of [16]annulenes and the 25 most stable Möbius stabilized [16]annulenes indicates that the compound of Figure 43 belongs to the cluster of aromatic Möbius [16]annulene systems [256].…”
Section: [16]annulenementioning
confidence: 97%
“…The synthesized Möbius ring lies ∼ 2 kcal/mol above and has the structure anti − tZcZcZt shown in Figure 43 with C 2 symmetry [255]. It has been argued [258] about aromaticity of this system, on the basis of the bond alternation resulting from crystal data [255] and of large dihedral angles inhibiting the overlap between π orbitals. In contrast, the principal component analysis performed on the 153 most stable structures of [16]annulenes and the 25 most stable Möbius stabilized [16]annulenes indicates that the compound of Figure 43 belongs to the cluster of aromatic Möbius [16]annulene systems [256].…”
Section: [16]annulenementioning
confidence: 97%
“…Thus, benzoannelation in these systems helps to stabilize the twist but does not diminish the aromatic character significantly, [5] which contradicts other purely theoretical work. [6] Interestingly, a detailed analysis of figure-eight-shaped expanded porphyrins was presented in a recent review by Herges dealing with the design of Möbius molecules.…”
Section: Aromaticity · Expanded Porphyrins · Möbius Aromaticity · Pormentioning
confidence: 99%
“…[15] In 2003, Herges and his co-workers reported a [16]annulene molecule as the first example of stable Mçbius aromatic molecule. [16] Even though these results were confronted with skeptical debates about aromatic character of that molecule, [17] this work boosted scientific interests towards Mçbius aromatic molecules. Along this line, Latos-Grażyń ski with his co-workers and our research group independently reported the first examples of Mçbius aromatic expanded porphyrins: di-p-benzi [28]hexaphyrin [12] and metal complexes of meso-aryl-substituted hexaphyrin, heptaphyrin, and octaphyrins, [13] respectively.…”
Section: Introductionmentioning
confidence: 99%